2020
DOI: 10.1111/wrr.12828
|View full text |Cite
|
Sign up to set email alerts
|

Pigment epithelium‐derived factor attenuates angiogenesis and collagen deposition in hypertrophic scars

Abstract: Scar forming wounds are often characterized by higher levels of vascularity than non‐scarring wounds and normal skin, and inhibition of angiogenesis has been shown to inhibit scar formation in some model systems. The rabbit ear hypertrophic scar (HS) model has been widely used to study the mechanisms that underlie the development of HS as well as the effectiveness of various treatments. Although the rabbit ear HS model is well characterized in terms of scar formation, the rate and level of angiogenesis has not… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 59 publications
(93 reference statements)
0
5
0
Order By: Relevance
“…6) 4 . Specifically, our reverse western blot array and cell migration data revealed that the combination of VEGF, HB-EGF, and PIGF-all of which are secreted by HLFs-work together to establish a pro-angiogenic cell culture environment, unlike MSCs, which are known as anti-inflammatory cell types secreting numerous anti-angiogenic factors, such as TIMP-1, PEDF, and TSP-1 [26][27][28][29][30][31][32] . Further research is required to identify the molecular mechanisms by which these four factors cooperatively promote angiogenesis and to develop the next generation of anti-angiogenic cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…6) 4 . Specifically, our reverse western blot array and cell migration data revealed that the combination of VEGF, HB-EGF, and PIGF-all of which are secreted by HLFs-work together to establish a pro-angiogenic cell culture environment, unlike MSCs, which are known as anti-inflammatory cell types secreting numerous anti-angiogenic factors, such as TIMP-1, PEDF, and TSP-1 [26][27][28][29][30][31][32] . Further research is required to identify the molecular mechanisms by which these four factors cooperatively promote angiogenesis and to develop the next generation of anti-angiogenic cancer therapeutics.…”
Section: Discussionmentioning
confidence: 99%
“…Reducing tension can not only promote the growth of immune cells, but also promote the regeneration of blood vessels, tissue regeneration accelerates and can also reduce scar formation. Hyperplastic scar is pathological scar caused by excessive synthesis and deposition of collagen [15]. Skin mechanical tension can cause fibroblast proliferation and transformation through various mechanisms, regulate protein excretion, inhibit apoptosis, induce pathological scar formation, and promote its proliferation and expansion.…”
Section: Resultsmentioning
confidence: 99%
“…Meanwhile, there is existing evidence indicating that excessive angiogenic response has been suggested to promote scar formation [ 59 ]. The involvement of angiogenesis in scar formation has been demonstrated in various models, including hypertrophic scars, traumatic brain injury, and myocardial infarction [ 60 , 61 , 62 ]. The promotion of angiogenesis has been shown to enhance scar formation in specific contexts, such as skin scarring and spinal cord injury [ 63 , 64 ].…”
Section: Discussionmentioning
confidence: 99%